Improving Self-Confidence, Enthusiasm, And Learning Satisfaction With mE-Book Practical Arabic Syntax and ARIAS Learning Model - Luthfi Anisatin; Moh. Khasairi; Nurhidayati Nurhidayati; Ali Mahmud Al-Asmai Ismail (Arabic Education Department, Islamic Studies Faculty, Universitas Muhammadiyah Malang, 2023)
This study aimed to determine the level of effectiveness of mE-Book practical Arabic syntax with the ARIAS learning model in increasing self-confidence, enthusiasm for learning, learning satisfaction, and student learning outcomes. The research method used is a quantitative approach with a one group pretest-posttest design model with data collection techniques in the form of observations, questionnaires, tests, and documentation. Data analysis techniques are obtained from the distribution of normality, hypothesis testing and n-gain. This research was conducted at ma'had Nurul Furqon Malang in grade X of high school with a total of 20 students. The results of the study prove that the use of mE-Book practical Arabic syntax with the ARIAS learning model can effectively increase self-confidence, student enthusiasm, learning satisfaction, and student learning outcomes.